The Nature of Hyperactivity in Children and Adolescents With Hydrocephalus: A Test of the Dual Pathway Model - Jim Stevenson; Ineke Pit-ten Cate (Neural Plasticity)
To determine the strength and nature of the association between hydrocephalus and hyperactivity and to test the dual pathway model (DPM) of AD/HD, we compared a group of 51 children and adolescents with hydrocephalus with 57 normally developing controls from the general population on a battery of neuropsychological assessments. The mean hyperactivity scores were significantly greater in the group with hydrocephalus (effect size =0.94). This association was not just part of a general elevated rate of behavior problems and was not affected by sex or age. Variation in the clinical features of hydrocephalus was not related to the severity of hyperactivity. Path analysis was used to examine the relation between IQ, delay aversion, and executive function. In accordance with the DPM, the effect of hydrocephalus on hyperactivity was completely mediated via delay aversion and executive functions.